The role of intravascular ultrasound in the management of spontaneous coronary artery dissection. - Arnold, JR; West, N; van Gaal, W; Karamitsos, T; Banning, A (2008)
Primary or spontaneous coronary artery dissection (SCAD) is an unusual but increasingly recognized cause of acute myocardial ischemia and sudden cardiac death. Typically, SCAD presents in younger patients without conventional risk factors for coronary artery disease. It occurs more commonly in women than in men, and frequently during pregnancy or the postpartum period. Its pathophysiology is poorly understood, and there is considerable controversy regarding the optimal management of patients with SCAD-related myocardial ischemia. Therapeutic approaches include conservative medical therapy, coronary artery bypass graft surgery and percutaneous coronary intervention (PCI). We present four cases of SCAD to illustrate specific aspects of the presentation and management of this condition, with particular reference to the importance of intravascular ultrasound (IVUS) to aid diagnosis and guide subsequent PCI.